Effects of different mixtures of maize and quinoa intercropping on grain yield and fatty acid composition of oil under water reduction - Yakup Onur KOCA; Yuksel AYDOGAN; Ilkay ALKAN; Talih GURBUZ (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
The objective of this study was to ascertain the impact of drought on quinoa (Chenopodium quinoa) and maize (Zea mays L.) grown in intercropping at varying mixing rates, which represents a model of sustainable agricultural food production under the Mediterranean climate. The experiment included plots with five different crop combinations (25% quinoa - 75% maize, 50% quinoa - 50% maize, and 75% quinoa - 25% maize) as well as monoculture (100% quinoa and 100% maize). To ensure drought stress, plots with half the water holding capacity of the soil (W2) were used in addition to the full water holding capacity of the soil (W1). Drought stress caused dramatic decreases in the seed yield of both crops. The addition of a low rate of quinoa (25%) to the cultivation plot did not have a significantly (less than 10%) negative effect on the maize yield, despite the reduction in the number of maize plants. Similarly, growing a low rate of maize (25%) between quinoa rows increased quinoa yield under both irrigation conditions (P <0.01). The Water Use Efficiency (WUE) and Irrigation Water Use Efficiency (IWUE) calculated from the 25% quinoa - 75% maize was very close to those of the 100% maize in the W1 condition. Besides, the values under W2 exceeded those of the maize monoculture. Furthermore, all mixed plots had greater land equivalence rate (LER) values (>1) than those grown alone. Drought stress significantly affected the composition of oil, increasing palmitic acid and decreasing oleic, linoleic, and linolenic acid. The findings demonstrate that under conditions of drought stress, intercropping of quinoa and maize can partially tolerate reductions in both the product quantity and the composition of oil. These results indicate a harmonious relationship between the plants, particularly when the mixing rates include 25% quinoa-75% maize and 75% quinoa-25% maize.